2011
DOI: 10.1371/journal.pone.0016397
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of the Deubiquitinating Domain of CYLD in Myelomonocytic Cells Attenuates Inflammatory Responses

Abstract: The cylindromatosis tumor suppressor (CYLD) is a deubiquitinating enzyme that has been implicated in various aspects of adaptive and innate immune responses. Nevertheless, the role of CYLD in the function of specific types of immune cells remains elusive. In this report we have used conditional gene targeting in mice to address the role of the deubiquitinating activity of CYLD in the myelomonocytic lineage. Truncation of the deubiquitinating domain of CYLD specifically in myelomonocytic cells impaired the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…We have demonstrated that loss of Cyld function does not affect NF-κB activity but enhances JNK activity in renal tubular epithelial cells contributing the tubulointerstitial inflammation of IgA nephropathy [33]. Notably, truncation of deubiquitinating domain of CYLD specifically in myelomonocytic cells suppresses the development of lethal LPS-induced endotoxic shock and the accumulation of thioglycollate-elicited peritoneal macrophages with hyperactivation of NF-κB [45]. Because the over-expression of exogenous CYLD may cover the endogenous function of CYLD in VSMCs [23], aforementioned, we believe that results obtained by Cyld loss-of-function RNAi approach reflects more precisely the intrinsic function of CYLD in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that loss of Cyld function does not affect NF-κB activity but enhances JNK activity in renal tubular epithelial cells contributing the tubulointerstitial inflammation of IgA nephropathy [33]. Notably, truncation of deubiquitinating domain of CYLD specifically in myelomonocytic cells suppresses the development of lethal LPS-induced endotoxic shock and the accumulation of thioglycollate-elicited peritoneal macrophages with hyperactivation of NF-κB [45]. Because the over-expression of exogenous CYLD may cover the endogenous function of CYLD in VSMCs [23], aforementioned, we believe that results obtained by Cyld loss-of-function RNAi approach reflects more precisely the intrinsic function of CYLD in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…A20 deficiency in B cells induces the expansion of myeloid and T cells, resulting in splenomegaly and chronic inflammation (11). It seems possible that loss of CYLD function in myelomonocytic cells, which impairs their responses to inflammatory stimuli (36), counteracts the inflammation caused by A20-deficient B cells to some extent. This could explain the reduction of splenocyte numbers in CD19Cre/A20 F/F CYLD 2/2 mice compared with CD19Cre/A20 F/F mice.…”
Section: Loss Of Cyld Does Not Exacerbate the Defects In A20-deficienmentioning
confidence: 99%
“…Furthermore, a conditional gene targeting approach was used to create CyldΔ9 mice, which has enhanced cell resistance to LPS-induced endotoxic shock, while the CYLD-deficient macrophages failed to accumulate to the inflammatory site. These results suggest potential benefits of targeting CYLD with inhibitors in control of certain forms of pathogenic inflammation [19]. …”
Section: The Host Immune Responses Regulated By Dubsmentioning
confidence: 99%